CLASSIFICATION OF PRIMARY AND SECONDARY PREDICATION IN LINGUISTIC STRUCTURES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the concepts of primary and secondary predication within linguistic theory, examining how different types of predicates convey core and supplemental information about the subject in a sentence. Primary predication is the fundamental relationship between subject and predicate, where the predicate directly expresses an action, state, or attribute of the subject. Examples include verbal, copular, and existential predication, each serving to establish the main assertion or characteristic of the subject. In contrast, secondary predication provides additional information that modifies or elaborates on the primary predication. Types of secondary predication include adverbial, resultative, causative, and concomitant predication, each offering contextual details like manner, result, cause, or simultaneous action. The article concludes that understanding these distinctions not only aids in syntactic analysis but also enriches one’s appreciation for the expressiveness and structure of language, enhancing both comprehension and communication.